PARADIGMA SOSIOLOGI TENTANG PERCERAIAN - Chris S. Oiladang (Jurnal Pluralis, 2024)
The Divorce is a social reality that get attention from every discipline of science and it as of course can be analyzed from every point of view. Sociology analyzes the divorce problem because it has sociology meaning in deep. The divorce becomes a sociology analyzing object besides it is full of sociology meaning, but the main point is the divorce can be analyzed from sociology paradigm point of view. Therefore can be proved this exixtence of the divorce as a social fact, the divorce is a social definition, and the divorce as a social behavior.